Manajemen Sumber Daya Manusia Dalam Meningkatkan Disiplin Kerja Dosen STAI Jamiatut Tarbiyah Lhoksukon Aceh Utara - Suci Wahyuni (Journal of Islamic Education and Law, 2026)
The research aims to analyze the application of human resource management (HRM) in improving the performance of lecturers at STAI Jamiatut Tarbiyah Lhoksukon. This study is a field study using a qualitative desciptive approach. The research sources consist of primary  and secondary data. The research collected data through observations, interviews, and documentation. Data analysis was conducted through data reduction, presenting data, and drawing conclusions from the coolected data, while ensuring the validity of the data using triangulation techniques with theory. The results of this study indicate that: (1) HRM planning in improving the performance of lecturers at STAI Jamiatut Tarbiyah Lhoksukon includes. (2) The implementation of HRM to ensure the capability of the lecturers at STAI Jamiatut Tarbiyah Lhoksukon includes training, career development, and lecturer compensation. (3) Human Resource Evaluation in Improving the Work Discipline of Lecturers at STAI Jamiatut Tarbiyah Lhoksukon, the results of the study indicate that the human resource evaluation process is carried out through various mechanisms, such as lecturer performance assessment (BKD), attendance monitoring, student evaluation of teaching, and academic supervision by institutional leaders.